2010
DOI: 10.1103/physrevlett.105.205301
|View full text |Cite
|
Sign up to set email alerts
|

Binary Quantum Turbulence Arising from Countersuperflow Instability in Two-Component Bose-Einstein Condensates

Abstract: We theoretically study the development of quantum turbulence from two counter-propagating superfluids of miscible Bose-Einstein condensates by numerically solving the coupled Gross-Pitaevskii equations. When the relative velocity exceeds a critical value, the countersuperflow becomes unstable and quantized vortices are nucleated, which leads to isotropic quantum turbulence consisting of two superflows. It is shown that the binary turbulence can be realized experimentally in a trapped system.PACS numbers: 03.75… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 20 publications
3
121
0
1
Order By: Relevance
“…In this turbulence, not only the velocity field but also the spin density vector field is disturbed, so we call it spin turbulence. Though QT in the binary [151,152,153,154,155,156,157] and spin-2 spinor BECs [136,158] have been studied, we do not address these in this review.…”
Section: Theoretical Studies Of Turbulence In Spinor Becsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this turbulence, not only the velocity field but also the spin density vector field is disturbed, so we call it spin turbulence. Though QT in the binary [151,152,153,154,155,156,157] and spin-2 spinor BECs [136,158] have been studied, we do not address these in this review.…”
Section: Theoretical Studies Of Turbulence In Spinor Becsmentioning
confidence: 99%
“…Recently, studies of QT in this system have been carried out [136,151,152,153,154,155,156,157,158], in which correlation functions for the velocity field and spin density vector were investigated and some power laws were reported. However, these address binary QT in limited parameter regions, and QT in a mass imbalance system or QT with spin-orbit coupling have never been investigated.…”
Section: Qt In a Binary Becmentioning
confidence: 99%
“…Together with the long lifetime of the observed dark-bright solitons, this opens the door to future experiments with these interesting coherent nonlinear structures. While the dynamics considered in this Letter are effectively one-dimensional, a very recent theoretical analysis has shown that superfluid counterflow in higher dimensions can lead to binary quantum turbulence, providing another example of the exceptional dynamical richness of the two-component system [21]. Fig.…”
mentioning
confidence: 99%
“…Employing such adjustability and selectability, intriguing phenomena that depend on the degree of miscibility have been experimentally observed, e.g., soliton generation in a counterflow of miscible fluids [8,9], quantum tunneling across spin domains [10] and suppression of relative flow by multiple domains [11] in immiscible systems. Theoretically, quantum turbulence in a counterflow of miscible BECs [12,13] and pattern formation by instabilities at interfaces in immiscible BECs [14][15][16][17][18] have been predicted.…”
mentioning
confidence: 99%